(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The psychology of juvenile delinquency involves a complex interplay of biological, psychological, and social factors that influence the behavior of adolescents who engage in criminal activities. Juveniles often display deviant behavior as a result of various internal and external factors, such as dysfunctional family environments, peer pressure, socioeconomic challenges, mental health issues, and the lack of proper role models. Adolescence is a critical stage in an individual’s development, and it is during this period that the foundations for moral and social behavior are laid. Psychological theories, such as the Social Learning Theory and Strain Theory, provide frameworks for understanding how juvenile behavior is shaped by their environment and experiences. Factors such as childhood trauma, neglect, and abuse can lead to feelings of anger, insecurity, and a lack of control, which may manifest in delinquent behavior. Moreover, peer influence and the desire for acceptance can drive juveniles to engage in criminal activities. Addressing juvenile delinquency requires a multifaceted approach that focuses on rehabilitation, mental health support, and creating a nurturing environment to help these individuals reintegrate into society. Effective intervention strategies include counseling, mentorship, and creating positive outlets for self-expression. Understanding the psychological underpinnings of delinquent behavior is crucial for designing effective prevention and intervention programs aimed at reducing juvenile crime.